Management information systems : managing the digital firm - Laudon, Kenneth C., 1944-2019; Laudon, Jane P. (Jane Price) (2022)
"Management Information Systems, 17th edition has been thoroughly updated to cover the latest industry and technology changes that impact the course"--
Sixteenth edition published 2019.
Includes bibliographical references and index.
Keywords: Management information systems; Management information systems -- Study and teaching